2021
DOI: 10.1055/s-0040-1721062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Homeopathic Treatment on the Quality of Life of Women with Chronic Diseases: A Randomized Controlled Pragmatic Trial

Abstract: Background Despite the increasing demand for complementary and integrative medicine, only a few studies have evaluated the effect of these types of treatments on the quality of life (QoL) of patients with chronic diseases. The objective of this study was to evaluate the QoL of women treated with homeopathy within the Public Health System of Belo Horizonte, Brazil. Methods This is a prospective randomized controlled pragmatic trial. The patients were divided into two independent groups, one group unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…A recent pragmatic, prospective, controlled, randomised and non-blinded trial performed by Champs and collaborators in a public outpatient clinic in Belo Horizonte, Brazil, showed that homeopathy had a positive impact on the quality of life and subjective perception of health of women with chronic diseases after 6 months of treatment. 19 This research finding corroborates previously published international non-randomised studies. 20,21 From the above, it is clear that homeopathy's individualised approach, with emphasis on healthy lifestyle guidance and having an expanded view of the health-disease process, contributes to perspectives on prevention, promoting health and improving the quality of life of individuals, making it a relevant therapeutic option for SUS users in Brazil.…”
Section: Individualisation With the Vision Of Totality: Principles Of...supporting
confidence: 92%
See 1 more Smart Citation
“…A recent pragmatic, prospective, controlled, randomised and non-blinded trial performed by Champs and collaborators in a public outpatient clinic in Belo Horizonte, Brazil, showed that homeopathy had a positive impact on the quality of life and subjective perception of health of women with chronic diseases after 6 months of treatment. 19 This research finding corroborates previously published international non-randomised studies. 20,21 From the above, it is clear that homeopathy's individualised approach, with emphasis on healthy lifestyle guidance and having an expanded view of the health-disease process, contributes to perspectives on prevention, promoting health and improving the quality of life of individuals, making it a relevant therapeutic option for SUS users in Brazil.…”
Section: Individualisation With the Vision Of Totality: Principles Of...supporting
confidence: 92%
“…A recent pragmatic, prospective, controlled, randomised and non-blinded trial performed by Champs and collaborators in a public outpatient clinic in Belo Horizonte, Brazil, showed that homeopathy had a positive impact on the quality of life and subjective perception of health of women with chronic diseases after 6 months of treatment. 19 This research finding corroborates previously published international non-randomised studies. 20 21…”
Section: Individualisation With the Vision Of Totality: Principles Of...supporting
confidence: 92%